Description of the final instar larvae of Acanthagrion gracile (Rambur) and Acanthagrion lancea Selys (Odonata: Coenagrionidae) - Anjos-Santos, Danielle; Carriço, César; Costa, Janira Martins; Santos, Tatiana Chrysostomo (Zootaxa, 2011)
The final instar larvae of Acanthagrion gracile and A. lancea are described and illustrated based on reared specimens from Rio de Janeiro and Espírito Santo States, Brazil, being compared with the other known larvae of this genus.